The Journal of Ethics An International Philosophical Review - Lemos, Noah.; Dubbink, Wim.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
The Journal of Ethics: An International Philosophical Review seeks to publish articles on a wide range of topics in ethics, philosophically construed, including such areas as ethical theory, social, political, and legal philosophy, applied ethics, meta-ethics, the metaphysics of morality, and the history of ethics. The Journal of Ethics publishes work from a wide variety of styles including but not limited to the analytic tradition and hermeneutics. The Journal of Ethics is also interested in ethical thinking that is enriched by psychology, sociology and other empirical disciplines. The Journal of Ethics is primarily an organ of philosophical research, although it publishes work on topics of concern to academics and professionals alike. The journal also seeks to publish the highest quality commentaries on works published in its pages. Its double-blind review process must ensure analytical acuity as well as depth and range of philosophical scholarship.
Keywords: Philosophy; Ethics; Political philosophy; Ethics; Political Philosophy; Philosophy, general